The effect of high vs. low carbohydrate diets on distances covered in soccer - Souglis, A. G.; Chryssanthopoulos, C. I.; Travlos, A. K.; Zorzou, A. E.; Gissis, I. T.; Papadopoulos, C. N.; Sotiropoulos, A. A. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to compare the distances covered during a 11-a-side soccer match after players had consumed either a high carbohydrate (CHO) or a low CHO diet. Twenty-two male professional soccer players formed 2 teams (A and B), of similar age, body characteristics, and training experience. The 2 teams played against each other twice with a week interval between. For 3.5 days before the first match, the players of team A followed a high CHO diet that provided 8 g CHO per kg body mass (BM) (HC), whereas team B players followed a low CHO diet that provided 3 g CHO per kg BM (LC) for the same time period. Before the second match the dietary treatment was reversed and followed for the same time period. Training during the study was controlled, and distances covered were measured using global positioning system technology. Every player covered a greater total distance in HC compared with the distance covered in LC (HC: 9,380 ± 98 m vs. LC: 8,077 ± 109 m; p < 0.01). All distances covered from easy jogging (7.15 km/h) to sprinting (24.15 km/h) were also higher in HC compared with LC (p < 0.01). When players followed the HC treatment, they won the match (team A vs. team B: 3-1 for the first game and 1-2 for the second game). The HC diet probably helped players to cover a greater distance compared with LC. Soccer players should avoid eating a low (3 g CHO per kg BM) CHO diet 3-4 days before an important soccer match and have a high CHO intake that provides at least 8 g CHO per kg BM.